2018
DOI: 10.1002/cctc.201801174
|View full text |Cite
|
Sign up to set email alerts
|

Single Atom Catalysts on Carbon‐Based Materials

Abstract: Metal particle size is an important parameter to consider when looking at supported catalyst performances. As for other properties, surface reactivity of metallic nanoparticles is thus highly size‐dependent. The smallest size that can be reached for this type of object is of course the isolated atom deposited on a support. The preparation of single‐atom catalysts (SAC) is not trivial, since to avoid clustering, the mean adsorption energy of the metal on the support should be higher than its cohesive energy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(108 citation statements)
references
References 337 publications
(260 reference statements)
4
102
0
Order By: Relevance
“…Recently, an intensive investigation toward SACs has triggered the development of advanced characterization techniques for the morphologies of catalytic materials and local coordination environments of single metal atoms. However, it is still hard to require comprehensive information derived from any single techniques . As we know, aberration‐corrected high‐angle annular dark‐field scanning transmission electron microscope (HAADF‐STEM), atomic‐resolution energy dispersive X‐ray spectroscopy, and electron energy loss spectroscopy can bring direct identification of the morphologies, structures, and compositions of active phases featured on carbon‐rich NPMSACs.…”
Section: Characterization and Evaluation Of Carbon‐rich Npmsacs For Cmentioning
confidence: 99%
“…Recently, an intensive investigation toward SACs has triggered the development of advanced characterization techniques for the morphologies of catalytic materials and local coordination environments of single metal atoms. However, it is still hard to require comprehensive information derived from any single techniques . As we know, aberration‐corrected high‐angle annular dark‐field scanning transmission electron microscope (HAADF‐STEM), atomic‐resolution energy dispersive X‐ray spectroscopy, and electron energy loss spectroscopy can bring direct identification of the morphologies, structures, and compositions of active phases featured on carbon‐rich NPMSACs.…”
Section: Characterization and Evaluation Of Carbon‐rich Npmsacs For Cmentioning
confidence: 99%
“…However, it was recently reported that g-C 3 N 4 generally can support a lower loading than graphene owing to its much stronger interlayer interactions [83]. Readers who are interested in g-C 3 N 4 -doped systems for catalysis are advised to consult other reviews found elsewhere [9,[87][88][89].…”
Section: Anchor Atoms To Stabilize the Supported Atomic Scale Catalystsmentioning
confidence: 99%
“…Recently, a variety of strategies have been developed to fabricate different single metal atoms on graphene as catalysts, which exhibit superior electrocatalytic properties in energy conversion and storage. Although there are several reviews that reported the fabrication of single atoms on carbon‐based materials, it is noted that there is no comprehensive review that focuses on the engineering of single atoms on graphene (SAG). In this review, we will summary the recent development of single metal atoms on graphene, including the fabrication strategies, characterization methods, and their electrocatalytic application in the energy conversion and storage, such as ORR, OER, HER, CO 2 RR, and methane oxidation was highlighted ( Figure ).…”
Section: Introductionmentioning
confidence: 99%